VOTO FACULTATIVO/OBRIGATÓRIO - Gonçalves, Carolina; Sanches, Claudinei Perea; Gabrielli, Nathalia; Oliveira, Júlio Cesar Claudio de; Moreira, Renato; Matos, Rogério Carvalho de; Silva, Marcos Antonio; Pina, Regina Maria (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver texto na íntegra.